2014
DOI: 10.1038/cddis.2014.275
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine alters cortical integration of GABAergic interneurons and induces long-term sex-dependent impairments in transgenic Gad67-GFP mice

Abstract: Ketamine, a non-competitive N-methyl-D-aspartate (NMDA) antagonist, widely used as an anesthetic in neonatal pediatrics, is also an illicit drug named Super K or KitKat consumed by teens and young adults. In the immature brain, despite several studies indicating that NMDA antagonists are neuroprotective against excitotoxic injuries, there is more and more evidence indicating that these molecules exert a deleterious effect by suppressing a trophic function of glutamate. In the present study, we show using Gad67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 54 publications
1
42
0
Order By: Relevance
“…To visualize neurons in ZI that contained GABA, coronal sections were processed for glutamic acid decarboxylase (GAD) using procedures adapted from previous reports (Oostland et al, 2011;Aligny et al, 2014). The sections were rinsed in 0.1 M PBS for 20 min before being placed in a PBS-based blocking solution that contained 0.3 M glycine, 5% goat serum, 1% bovine serum albumin, and 0.1% Triton X-100, pH 7.4, at room temperature for 1 h. Sections were then incubated overnight with polyclonal rabbit anti-GAD 65/67 antibody (1:250, ab49832, Abcam) diluted in PBS at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…To visualize neurons in ZI that contained GABA, coronal sections were processed for glutamic acid decarboxylase (GAD) using procedures adapted from previous reports (Oostland et al, 2011;Aligny et al, 2014). The sections were rinsed in 0.1 M PBS for 20 min before being placed in a PBS-based blocking solution that contained 0.3 M glycine, 5% goat serum, 1% bovine serum albumin, and 0.1% Triton X-100, pH 7.4, at room temperature for 1 h. Sections were then incubated overnight with polyclonal rabbit anti-GAD 65/67 antibody (1:250, ab49832, Abcam) diluted in PBS at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…By comparison, POm receives inputs from the trigeminal nuclei and sensorimotor cortex (Veinante et al, 2000;Alloway et al, 2003). Synchronous inputs from these sources increase POm responsiveness (Groh et al, 2014), which could contribute to the slow adaptation observed in POm.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations